Digital Marketing System for Jombang's Cultural Diversity and Tourism Based on a Website - Saputra, Rizky Dwi; Sufaidah, Siti (NEWTON: Networking and Information Technology, 2024)
Jombang Regency, East Java, has significant potential in the tourism and cultural sectors; however, the promotion and marketing of tourist destinations in this area remain limited. This Final Project report discusses the development of a website-based digital marketing system designed to enhance exposure and access to information about various tourist and cultural destinations in Jombang Regency. The system is equipped with features such as comments, ratings, and location maps, which facilitate users in discovering and exploring the available destinations. The objective of this research is to implement an effective digital marketing strategy to increase the number of tourists visiting Jombang Regency. The system, developed using PHP and MySQL, provides accurate and engaging information about natural, religious, popular, and historical tourist destinations in Jombang. The research findings indicate that the implementation of this system can enhance the visibility of tourist destinations in Jombang and significantly contribute to local economic growth. Through integrated and sustainable digital marketing, it is hoped that Jombang Regency can become one of Indonesia's leading tourist destinations, widely recognized both nationally and internationally.